Students Motivation toward the Use of Informatics Technology in Teaching English at MA Ma’arif Roudlotut Tholibin - Wulandari, Retno; Umar Al Faruq A Hasyim; Yeasy Agustina Sari; Riyan Erwin Hidayat; Suhono, Suhono (CV. Creative Tugu Pena, 2024)
The purpose of this research to analyze whether WhatsApp has an effect on increasing student motivation in Civic education. This research was quantitative research that conducted at MA Ma’arif Roudlotut Tholibin North Metro, with the research population that is all students of class X. The sample size of the study was 15 students determined by the Slovin formula, then the sample was taken in each class using random sampling technique. Data is collected via google form and distributed via WhatsApp. Data analysis was performed using descriptive analysis and simple linear regression. The result showed that online learning through WhatsApp group had an effect on increasing the motivation to learn Bahasa Inggris. The use of affordable data packages and the features offered by the WA application means that this application is not only used for communication by the public but is also widely used to support the implementation of education.